Towards the total synthesis of garsubellin A - Brochu, Marie-Christine (University of Ottawa (Canada), 2009)
Our laboratory reported a novel method to prepare highly oxygenated and functionalized bicyclo[m.n.l]alkanones from acetals using a Lewis acid mediated Prins-pinacol cationic cascade1. This allows us to access complex bridgehead ketone frameworks encountered in many natural products. Garsubellin A is an example of highly functionalized bicyclo[3.3.1]alkanone that we expect to synthesized using the Prins-pinacol methodology. For instance, we were able to prepare diastereoselectively an advanced intermediate for the total synthesis of garsubellin A using this method. Even if the Lewis acid mediated Prins-pinacol cationic cascade appears to be a powerfull method to access complex bridgehead ketone frameworks, we are presently envisaging a second method for the preparation of the garsubellin A core. This method consists in a gold catalyzed Conia-ene reaction. It was already demonstrated in our laboratory that unsubstituted bicyclo[3.3.1]alkanone can be prepared using the gold catalyzed Conia-ene reaction. We want to apply this new methodology to the total synthesis of garsubellin A.
Keywords: Chemistry, Organic.